Principles of digital image processing : advanced methods - Burger, Wilhelm; Burge, Mark J. (Undergraduate topics in computer science, 2013)
This book offers key concepts and methods in image processing, examples and exercises, Java code and worked-out examples for easy inclusion in existing applications, and a supplementary website with complete Java source code, test images, and corrections